SOIL RECOVERY WITH THE AGROFORESTRY SYSTEM - Moraes, João Antonio Tonon; Cavichiolli, Fábio Alexandre (Revista Interface Tecnológica, 2022)
Although it has been widely needed for some time, the recovery of degraded areas in Brazil is a recent activity. Before the emergence and evolution of the techniques used, soil recovery activities were based only on planting trees. In view of several studies, the techniques currently used consist of broad evolutions of programs aimed at environmental recovery, which seek to adapt the biodiversity of existing ecosystems in certain regions. The objective of this study is to evidence the recovery of the soil with the agroforestry system. The methodology used in this study is a literature review, with consultations carried out in online articles. The results show that the use of agroforestry systems for soil recovery has shown efficiency.